DNA typing from skeletal remains using GlobalFiler™ PCR amplification and Investigator® 24plex QS kits. Issue 1 (December 2019) - Zgonjanin, Dragana; Nedić, Dalibor; Alghafri, Rashed; Petković, Stojan; Vuković, Radenko
Abstract: Since the beginning of our work in 2003 our laboratory has focused exclusively on STR DNA from bone, a powerful tool in missing person cases. In cases such as mass disasters or missing persons, human remains are challenging to identify as they may be fragmented, burnt, recovered from water, degraded, and/or contain inhibitory substances. To address these challenges, this study has evaluated the performance of relatively new STR kits Investigator® 24plex QS kit (Qiagen) and GlobalFiler™ PCR Amplification kit (Thermo Fisher Scientific) by comparing it with current uses of the AmpFLSTR® Identifiler® Plus kit (Applied Biosystems) to obtain genetic information from skeletal remains. We analyzed 20 bone samples of skeletal remains from routine casework submitted for body identifications by law enforcement corresponding using Investigator® 24plex QS kit and GlobalFiler™ PCR Amplification kit, previously analysed AmpFLSTR® Identifiler® Plus kit (Thermo Fisher Scientific). The data indicates that the STR profiles obtained using the GlobalFiler™ and Investigator® 24plex QS kit for analysis of skeletal remains has shown results in an increased number of reportable genetic loci, and provide greater power of discrimination in comparison to the Identifiler® Plus Kit. Advanced extraction and purification techniques, together with more sensitive and robust new amplification kits allowed us to overcome the challenges associated with processing compromised skeletal remains and ultimately obtain full STR DNA profiles in 99% of the bones.